Structural and metabolic changes in rhizophores of the Cerrado species Chrysolaena obovata (Less.) Dematt. as influenced by drought and re-watering - Garcia, Paola M.; Hayashi, Adriana H.; Silva, Emerson A.; Figueiredo-Ribeiro, Rita de Cássia L.; Carvalho, Maria Angela M. (Frontiers in Plant Science, 2015)
The high fructan contents in underground organs of Cerrado species, high water solubility and fast metabolism of these compounds highlight their role as carbon storage and as an adaptive feature in plants under drought. In this study, we showed that anatomical structure, in association with soluble compounds and metabolism of inulin-type fructans were modified in rhizophores of Crysolaena obovata submitted to water suppression and recovery after re-watering. Plants were subjected to daily watering (control), suppression of watering for 22 days (water suppression) and suppression of watering followed by re-watering after 10 days (re-watered). Plants were collected at time 0 and after 3, 7, 10, 12, 17 and 22 days of treatment. In addition to changes in fructan metabolism, high proline content was detected in drought stressed plants, contributing to osmoregulation and recovery after water status reestablishment. Under water suppression, total inulin was reduced from approx. 60 to 40%, mainly due to exohydrolase activity. Concurrently, the activity of fructosyltransferases promoted the production of short chain inulin, which could contribute to the increase in osmotic potential. After re-watering, most parameters analyzed were similar to those of control plants, indicating the resumption of regular metabolism, after water absorption. Inulin sphero-crystals accumulated in parenchymatic cells of the cortex, vascular tissues and pith were reduced under drought and accompanied anatomical changes, starting from day 10. At 22 days of drought, the cortical and vascular tissues were collapsed, and inulin sphero-crystals and inulin content were reduced. The localization of inulin sphero-crystals in vascular tissues of C. obovata, as well as the decrease of total inulin and the increase in oligo: polysaccharide ratio in water stressed plants is consistent with the role of fructans in protecting plants against drought.